Molecular architectures of centrosomes in C. elegans embryos visualized by cryo-electron tomography - Tollervey, Fergus; Rios, Manolo U.; Zagoriy, Evgenia; Woodruff, Jeffrey B.; Mahamid, Julia (Developmental cell, 2025)
Centrosomes organize microtubules that are essential for mitotic divisions in animal cells. They consist of centrioles surrounded by pericentriolar material (PCM). Questions related to mechanisms of centriole assembly, PCM organization, and spindle microtubule formation remain unanswered, partly due to limited availability of molecular-resolution structural data inside cells. Here, we use cryo-electron tomography to visualize centrosomes across the cell cycle in cells isolated from C. elegans embryos. We describe a pseudo-timeline of centriole assembly and identify distinct structural features in both mother and daughter centrioles. We find that centrioles and PCM microtubules differ in protofilament number (13 versus 11), which could be explained by atypical γ-tubulin ring complexes with 11-fold symmetry identified at the minus ends of short PCM microtubule segments. We further characterize a porous and disordered network that forms the interconnected PCM. Thus, our work builds a three-dimensional structural atlas that helps explain how centrosomes assemble, grow, and achieve function.